A New Mechanism of Free-Radical Nonbranched-Chain Oxidation: Oxygen as an Antioxidant (International Journal of Innovative Research in Computer Science & Technology, 2017)
New reaction scheme is suggested for the initiated  nonbranched-chain addition of free radicals to the multiple bond of the molecular oxygen. The scheme includes the addition  reaction of the peroxyl free radical to the oxygen molecule to  form the tetraoxyl free radical. This reaction competes with  chain propagation reactions through a reactive free radical. The  chain evolution stage in this scheme involves a few of free  radicals, one of which (tetraoxyl) is relatively low-reactive and  inhibits the chain process by shortening of the kinetic chain  length. Based on the proposed scheme rate equations  (containing one to three parameters to be determined directly)  are deduced using quasi-steady-state treatment. The kinetic  description with use the obtained rate equations is applied to the  γ-induced nonbranched-chain processes of the free-radical  oxidation of liquid o-xylene at 373 K and hydrogen dissolved in  water containing different amounts of oxygen at 296 K. The  ratios of rate constants of competing reactions and rate constants  of addition reactions to the molecular oxygen are defined. In  these processes the oxygen with the increase of its concentration  begins to act as an oxidation autoinhibitor (or an antioxidant),  and the rate of peroxide formation as a function of the dissolved  oxygen concentration has a maximum. From the energetic  standpoint possible nonchain pathways of the free-radical  oxidation of hydrogen and the routes of ozone decay via the  reaction with the hydroxyl free radical in the upper atmosphere.
Keywords: competition; energy; hydrogen; thermochemical data.; low-reactive radical